Аpplication of the laccase, produced on coconut flesh by Pleurotus Florida for dye decolorization - Balan, K.; Pratheebaa, P.; Palvannan, T. (Химия и технология воды, 2013)
We investigated the ability of Pleurotus florida to produce laccase on coconut flesh as a solid substrate fermentation. The decolorization of two structurally different dyes such as azo (Reactive Blue 198) and triphenylmethane dye (Malachite Green) were analysed. The decolorization of Reactive blue 198 and Malachite Green at 8 hrs was 93% and 63% respectiely. The untreated and treated dye was characterized by UV-Vis and fourier transform infrared (FTIR) spectroscopy scan. FTIR analysis pointed out the involvement of alkene (C = C) and carboxylic (C – O) groups in the decolorization process. The toxicity with respect to Allium cepa root inhibition was measured to demonstrate the potential of laccase in the detoxication and bioremediation process. The Corresponding author (Principal Investigator – Project No.: BT/PR8973/GBD/27/57/2006 Dt 14/08/07) is grateful to Government of India, Ministry of Science and Technology, Department of Biotechnology for financial support.